A comparative analysis of unilateral biportal endoscopic and open laminectomy in multilevel lumbar stenosis - Ouyang, Jian-yuan; Yang, Qi-Yuan; Chen, Lan-lan; Li, Qin; Zheng, Yu-hao; Luo, Xiao; Tan, Bing (Frontiers in Neurology, 2024)
BackgroundApproximately 103 million people across the globe suffer from symptomatic lumbar spinal stenosis, impacting their health and quality of life. The unilateral biportal endoscopic technique is effective for treating single-segment degenerative lumbar spinal stenosis and is seen as a viable alternative to traditional open lumbar laminectomy. However, research on the application of this technique for multilevel lumbar spinal stenosis remains lacking.ObjectiveTo compare the clinical effects of unilateral biportal endoscopy (UBE) and open lumbar decompression (OLD) in the treatment of multilevel lumbar spinal stenosis (MLSS).MethodsThis retrospective study was conducted from February 2019 to December 2023 and compared the outcomes of Multilevel UBE surgery to OLD. The included patients were divided into two groups, namely the UBE group (n = 42, 86 surgical segments) and the OLD group (n = 40, 82 surgical segments). At the 1-year follow-up, the imaging findings, visual analogue scale (VAS), Oswestry disability index (ODI), and Zurich Claudication Questionnaire (ZCQ) were assessed. MRI measurements of the dural sac (CSA) and paravertebral cross-sectional area (PMA) were taken before surgery and at the final follow-up.ResultsThe surgical segments of the two groups primarily consisted of adjacent segments (UBE 78.6% vs. OLD 78.8%), with a higher proportion of bilateral decompression in the OLD group (UBE 24.4% vs. OLD 28.0%). Preoperative imaging evaluation indicated a higher prevalence of grade C (severe stenosis) compared to grade D (severe stenosis) in both groups (UBE 74.4% vs. OLD 72%). The OLD group exhibited significantly greater blood loss compared to the UBE group (147.63 ± 26.55 vs. 46.19 ± 25.25 mL, p < 0.001). In addition, the duration of hospitalization in the OLD group was notably longer compared to the UBE group (7.58 ± 1.39 vs. 4.38 ± 1.56 days, p < 0.05). Paravertebral muscle atrophy (PMA) in the UBE group was significantly lower than in the OLD group (3.49 ± 3.03 vs. 5.58 ± 3.00, p < 0.05). Significantly elevated serum creatine kinase (CK) levels were observed in both groups, peaking at 1-day post-surgery, with the UBE group showing significantly lower levels than the OLD group (108.1 ± 12.2 vs. 364.13 ± 20.24 U/L, p < 0.05). On postoperative day 7, a significant decrease in liver enzyme levels was found in UBE group compared to the preoperative levels (61.81 ± 7.14 vs. 66.10 ± 8.26 U/L, p < 0.05). The Oswestry Disability Index (ODI) and Zurich Claudication Questionnaire (ZCQ) scores at 1 week, 6 months, and 1 year post-operation showed significant improvement compared to the preoperative scores in both groups (p < 0.05). The study found statistically significant differences in both the Visual Analog Scale (VAS) score (2.28 ± 0.59 vs. 2.85 ± 0.74, p < 0.05) and the Oswestry Disability Index (ODI) score (36.28 ± 2.03 vs. 37.57 ± 1.98, p < 0.05) at 1 week post-surgery between the two groups. However, no significant variations in scores were noted between preoperative and postoperative time points at other follow-up intervals.ConclusionThe unilateral biportal endoscopic technique was applied to treat multilevel lumbar spinal stenosis, demonstrating decreased intraoperative bleeding and lower postoperative muscle-related complications compared to open lumbar decompression. Furthermore, UBE was found to promote early mobilization.